Embedded high‐precision capacitor measurement system based on ring‐oscillator. Issue 6 (1st March 2015) - Welter, L.; Dreux, P.; Aziza, H.; Portal, J.‐M.
Abstract : A direct way to measure the electrical value of capacitors embedded in a circuit using a ring‐oscillator is presented. A calibration system ensures the robustness of the measurement process against temperature, power supply and process variations. Silicon results show the ability of the system to measure robustly a large range of small capacitors. The system also provides a noise immunity as the system provides a digital signature of the capacitor value.